2010
DOI: 10.1080/00103624.2010.518263
|View full text |Cite
|
Sign up to set email alerts
|

Growth, Root Characteristics, and Leaf Nutrients Accumulation of Four Faba Bean (Vicia fabaL.) Cultivars Differing in Their Broomrape Tolerance and the Soil Properties in Relation to Salinity

Abstract: The effects of salinity on four faba bean (Vicia faba L) cultivars [Giza 429, Giza 843,, and Giza 3 (Orobanche-susceptible)] and soil properties were investigated in a pot experiment with addition of 0, 50, and 100 mM sodium chloride (NaCl) for 9 weeks. Salinity significantly decreased calcium (Ca 2+ ), magnesium (Mg 2+ ), potassium (K + ), bicarbonate (HCO 3 − ), and sulfate (SO 4 2− ) while significantly increasing sodium (Na + ), chloride (Cl − ), pH, and electrical conductivity (EC; dS m −1 ). Root length … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
34
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(41 citation statements)
references
References 38 publications
(38 reference statements)
7
34
0
Order By: Relevance
“…Previous researches have shown that varying levels of salinity significantly increased Na + concentration in four faba bean cultivars (Abdelhamid et al. ), five diverse cultivars of Brassica rapa (Noreen et al. ) and six soya bean accessions (Lenis et al.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…Previous researches have shown that varying levels of salinity significantly increased Na + concentration in four faba bean cultivars (Abdelhamid et al. ), five diverse cultivars of Brassica rapa (Noreen et al. ) and six soya bean accessions (Lenis et al.…”
Section: Discussionmentioning
confidence: 98%
“…), in addition to the inhibitory effect of the accumulated ions (Abdelhamid et al. , Dawood et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is more sensitive to salinity during early vegetative stages (Al-Tahir and Al-Abdulsalam, 1997), and reduction in growth can be as much as 50 percent at 6.7 dS m -1 salinity (Maas and Hoffman, 1977). In Egypt, broad bean is usually produced in saline soils (Abdelhamid et al, 2010). The prospect of limited fresh water in the country also limits the potential increase of broad bean production.…”
Section: Introductionmentioning
confidence: 99%